2018
DOI: 10.9734/arrb/2018/37443
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histochemical Characterization of the Midgut of Healthy Aedes aegypti Larvae

Abstract: This work was carried out in collaboration between all authors. Author ABL was responsible for developing all steps of this work and wrote the first draft of the manuscript. Author FCA helped with the histological methodology. Author KRSM was responsible for helping in histological and histochemical characterization. Author LBM offered his laboratory for cutting the histological material and author OSS was responsible for supervising the research. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…quinquefasciatus larvae from Jakarta were focused on changes in the activity of AChE, GST, and oxidase after exposure to these insecticides using a biochemical method ( Brogdon, 2014 ; Belmert et al., 2014 ). The histological damage of the midgut of these larvae was examined by a routine histopathological method ( de Lemos et al., 2018 ) and transmission electron microscopy (TEM) ( Ma et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…quinquefasciatus larvae from Jakarta were focused on changes in the activity of AChE, GST, and oxidase after exposure to these insecticides using a biochemical method ( Brogdon, 2014 ; Belmert et al., 2014 ). The histological damage of the midgut of these larvae was examined by a routine histopathological method ( de Lemos et al., 2018 ) and transmission electron microscopy (TEM) ( Ma et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A routine histopathological technique was employed as previously described [29]. In total, 150 dead Cx.…”
Section: Toxicity Of Op and Pyrmentioning
confidence: 99%
“…This study demonstrated that temephos, malathion, cypermethrin, and deltamethrin caused changes in the activity of AChE, GST, and oxidase in Cx.quiqnuefasciatus larvae. To prove that temephos, malathion, cypermethrin, and deltamethrin showed toxicity in the digestive system [17], the midgut damage of Cx.quinquefasciatus larvae exposed to the tested insecticides was observed by the routine histopathological method [29] and transmission electron microscopy (TEM) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Citronellal merupakan komponen utama minyak atsiri yang bekerja sebagai racun kontak dan racun perut. 14 Jenis tanaman atau tumbuhan yang dapat menyebabkan perubahan histopatologis sel epitel midgut larva Ae. aegypti beserta mekanisme kerja diantaranya adalah:…”
Section: Minyak Atsiriunclassified